Effects of a Specific Proprioceptive Training Program on Injury Prevention and Stress in Basketball Players: A Pilot Study - Vincenzo Cristian Francavilla; Giuseppe Messina; Omar Mingrino; Maria Chiara Parisi; Donatella Di Corrado (Journal of Functional Morphology and Kinesiology)
Background: Basketball carries a high risk of both chronic and acute musculoskeletal injuries, affecting various parts of the body. Additionally, stress is a critical factor that influences athletic performance, particularly in high-pressure sports like basketball. This study aimed to investigate the impact of a specific proprioceptive training protocol on professional basketball players. Methods: Thirty male basketball players (M = 21.93, SD = 3.75 years) were divided into two groups: an experimental group (n = 15) and a control group (n = 15). The experimental group completed an adapted proprioceptive training program designed to enhance position-specific skills, following their regular team training. The control group continued to follow their routine training program without any additional proprioceptive intervention. The parameters assessed included stress levels, longitudinal body axis alignment, spinal range of motion, and total plantar load distribution. These were measured at three time points: baseline (T0), after 4 weeks of training (T1), and after 8 weeks of training (T2). Results: Data analysis showed a significant reduction in stress (p < 0.001), postural alignment (p < 0.001), and spinal range of motion (p < 0.001) in the experimental group compared to the control group. Conclusions: In conclusion, the findings highlight the effectiveness of specific and detailed training programs in injury prevention, offering valuable insights for coaches and sports psychologists.